Use cases and scenarios of 5G integrated satellite‐terrestrial networks for enhanced mobile broadband: The SaT5G approach - Liolis, Konstantinos; Geurtz, Alexander; Sperber, Ray; Schulz, Detlef; Watts, Simon; Poziopoulou, Georgia; Evans, Barry; Wang, Ning; Vidal, Oriol; Tiomela Jou, Boris; Fitch, Michael; Diaz Sendra, Salva; et al. (International journal of satellite communications and networking, 2019)
Summary This paper presents initial results available from the European Commission Horizon 2020 5G Public Private Partnership Phase 2 project “SaT5G” (Satellite and Terrestrial Network for 5G). After describing the concept, objectives, challenges, and research pillars addressed by the SaT5G project, this paper elaborates on the selected use cases and scenarios for satellite communications positioning in the 5G usage scenario of enhanced mobile broadband. This paper presents initial results available from the SaT5G project. It describes the concept, objectives, challenges, and research pillars addressed by the SaT5G project. It also defines how satellite can be seamlessly integrated into the eMBB usage scenario for 5G, by elaborating on the SaT5G use cases and scenarios for satellite positioning in eMBB.